Radiological study of three cases of loose bodies in the temporomandibular joint - Allan Abuabara; Dale A. Miles; Giuseppe V. Cruz; Luis A. Passeri (Universidade Estadual de Campinas, 2015)
According to the literature, loose bodies in the temporomandibular joint (TMJ) primarily prompt to synovial chondromatosis (SC). SC is a cartilaginous metaplasia of the mesenchymal remnants of the synovial tissue of the joints. Its main characteristic is the formation of cartilaginous nodules in the synovium and inside the articular space, described as loose bodies. The main symptoms are pain, limitation of jaw movement, crepitation and inflammation. Diagnosis is made by panoramic radiograph, computed tomography scan and mainly magnetic resonance imaging. SC is usually monoarticular. We report two cases of bilateral loose bodies in TMJ and one monoarticular evaluated through plain radiograph and cone beam volumetric tomography (CBVT). Clinical and radiologic findings are reviewed and discussed. References for diagnosis of SC affecting TMJ are supported. Patients presenting preauricular swelling, pain and restriction of TMJ movements should be evaluated with plain radiography, CBVT and if necessary, magnetic resonance imaging. If loose bodies are found, synovial chondromatosis must be the first suspicion. The definitive diagnosis depends on histology. A differential diagnosis of chondrosarcoma should be considered because of the life-threatening features of chondrosarcoma.